Vertical Integration and Downstream Collusion - Sara Biancini; David Ettinger (Center for Economic Studies and ifo Institute (CESifo), 2016)
We investigate the effect of a vertical merger on downstream firms' ability to collude in a repeated game framework. We show that a vertical merger has two main effects. On the one hand, it increases the total collusive profits, increasing the stakes of collusion. On the other hand, it creates an asymmetry between the integrated firm and the unintegrated competitors. The integrated firm, accessing the input at marginal cost, faces higher profits in the deviation phase and in the non cooperative equilibrium, which potentially harms collusion. As we show, the optimal collusive profit-sharing agreement takes care of the increased incentive to deviate of the integrated firm, while optimal punishment erases the difficulty related to the asymmetries in the non cooperative state. As a result, vertical integration generally favors collusion.
Keywords: D43; L13; L40; L42; 330; vertical integration; tacit collusion